CRAN-16. IMPORTANCE OF SURGICAL INTERVENTION IN RECOVERY OF VISUAL FUNCTION IN A TEENAGER WITH AN ACIDOPHILIC STEM CELL ADENOMA. Issue 2 (22nd June 2018) - Johnson, Courtney; Jane, John; Vaidyanathan, Priya; Kwok, Young; Stasheff, Steven; Packer, Roger; Hwang, Eugene
Abstract: BACKGROUND: Prolactin-secreting macroadenomas are generally not life-threatening and often present with visual impairment. Medical management with a dopamine agonist is typically the treatment of choice, which significantly reduces the tumor size and improves symptoms without surgical morbidity. In this report, we present a case of an acidophilic stem cell adenoma (ASCA) that was slowly responsive to medical management, but exhibited marked visual recovery after surgical resection. RESULTS: A 15 year-old previously healthy male presented with significantly decreased peripheral vision but no other neurologic or endocrinologic symptoms. Initial magnetic resonance imaging of the brain/spine revealed a mass in the suprasellar and sellar regions with extension into the cavernous sinus and a prolactin level of 644, leading to a presumptive diagnosis of macroprolactinoma. Medical management with cabergoline resulted in some decrease of the prolactin level, but no radiographic improvement or visual recovery after two months. He subsequently underwent endoscopic endonasal transsphenoidal resection with near-total restoration of his peripheral vision post-operatively and significant improvement of his prolactin level. Pathology was consistent with an ASCA (staining positively with prolactin, growth hormone (a-subunit), and pituitary-specific positive transcription factor 1), a rare pituitary adenoma that tends to be invasive and often requires more aggressive therapy; the patient thus underwent focal consolidative proton beam irradiation. CONCLUSION: This case highlights the importance of considering acidophilic stem cell adenomas in the differential of medically-resistant pituitary macroadenomas and early consideration of resection in cases where significant visual or other symptoms exist, as timely intervention may substantially improve functional outcomes.